2019
DOI: 10.1002/etc.4427
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Exposure Routes of Fluvalinate to Larval and Adult Honey Bees ( Apis mellifera )

Abstract: Fluvalinate has been extensively used in the United States to combat honey bee colony loss due to Varroa destructor mites. Our objectives were to investigate the extent of fluvalinate contamination in commercially available wax and to define exposure pathways to larval and adult honey bees. All the commercial wax tested contained elevated fluvalinate concentrations, indicating a need for regulation of the sources of wax being rendered for resale. Based on the negative logarithm of the partition coefficient bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…For each residue detected in beeswax, a transfer rate to each of the hive matrices should have been determined experimentally. To our knowledge, this work has only been done for fluvalinate between wax and pollen by Fulton et al (2019) and for seventeen different pesticides between wax and honey by Shimshoni et al (2019). Fulton et al (2019) have determined a Log K wp value (with 'wp' meaning 'wax/ pollen') of −0.54 for fluvalinate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For each residue detected in beeswax, a transfer rate to each of the hive matrices should have been determined experimentally. To our knowledge, this work has only been done for fluvalinate between wax and pollen by Fulton et al (2019) and for seventeen different pesticides between wax and honey by Shimshoni et al (2019). Fulton et al (2019) have determined a Log K wp value (with 'wp' meaning 'wax/ pollen') of −0.54 for fluvalinate.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this work has only been done for fluvalinate between wax and pollen by Fulton et al (2019) and for seventeen different pesticides between wax and honey by Shimshoni et al (2019). Fulton et al (2019) have determined a Log K wp value (with 'wp' meaning 'wax/ pollen') of −0.54 for fluvalinate. It is noteworthy that this value should be compared to 3.85, the Log K ow (=Log P) for fluvalinate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, beekeepers are largely reliant on chemical acaricides to control Varroa despite the dangers that these chemicals pose to bees and the ongoing issues with chemical resistance in the mites. These acaricides have been linked to numerous honey bee health problems, and many studies have shown that residues can accumulate in the hive over time [24][25][26] . Unintended effects on honey bees include increased mortality in brood and adults 27 and an increased susceptibility to pathogens and agrichemicals [28][29][30] .…”
mentioning
confidence: 99%